THE INFLUENCE OF PRODUCT QUALITY, PRICE AND ELECTRONIC WORD OF MOUTH ON THE PURCHASE DECISION OF MS GLOW SKINCARE - Mutia Arda; Dewi Andriany (RADJA PUBLIKA, 2023)
Skincare is a very important product for the skin, so consumers are very picky in choosing the best quality products according to their skin type. One of the most popular skin care products in Indonesia today is the Ms Glow skin care product. Based on the reviews given by consumers on marketplaces and social media, it was found that there were still many consumers who were not suitable for these skincare products and when compared to the prices of some competitors, MS Glow skincare tended to be more expensive. The purpose of this study was to analyze the influence of product quality, price and electronic word of mouth on purchasing decisions for Ms Glow Skincare. The method used in this research is to use associative and quantitative methods. The number of samples is 98 people using the Slovin formula. Data collection techniques through questionnaires (questionnaire). Analysis of the research data is multiple linear regression. The results of this study indicate that product quality, price and electronic word of mouth simultaneously have a significant effect on purchasing decisions for Ms Glow Skincare. Partially product quality, price and electronic word of mouth have a significant effect on purchasing decisions.